Structural and functional changes of the heart in patients with coronary heart disease who have had coronavirus disease COVID-19 - S. M. Manuilov; N. S. Mykhailovska (Сучасні медичні технології)
The aim of the study: to investigate the effect of the previous COVID-19 coronavirus disease on the features of cardiac remodeling in patients with coronary heart disease (CHD).